E-Modul IPAS Berbasis Aplikasi Flip PDF Corporate Untuk Mendukung Implementasi “Kurikulum Merdeka” di Sekolah Dasar - Ira Oktaviani; Desyandri Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This research is motivated by the lack of interest in the teaching materials used in elementary schools. The aim of the research is to produce valid and practical e-modules using Corporate Flip Pdf in supporting the successful implementation of the "Independence Curriculum" in Elementary School classes. This type of research is development research (R&D) with the ADDIE model with the stages of analysis, planning, development, implementation and evaluation. The usefulness of digital modules is validated by validity tests and e-module practicality tests. Validity data sourced from learning material experts 79.09%, media experts 87.99%, language experts 90%, and expert practitioners by "driving teachers" 92%. The average validation score is 87.46% with a very valid category. The practicality test was obtained through a questionnaire given to teachers at 93.75% and students at 97.28%. The average practicality test result is 95.52% in the very practical category. Thus, the results of the study show that the e-module that has been developed using Flip Pdf Corporate is very feasible and practical to use in elementary schools.